Analisis Peran Pemerintah Dan Akademisi Terhadap Pengembangan Usaha Mikro Kecil Dan Menengah (UMKM) Provinsi Papua Pegunungan - vianney, Lazarus Suyatno (Universitas Pahlawan Tuanku Tambusai, 2024)
This research aims to determine the role of government and academics in the development of micro, small and medium enterprises (MSMEs) in Papua Mountains Province. This study uses a descriptive approach with a quantitative method with a data collection technique, namely distributing questionnaires. The results of this study conclude that the role of the regional government of Papua Mountains Province has a significant influence on the development of micro, small and medium enterprises (MSMEs). Intervention or the role of the regional government, especially in the form of capital assistance, has been proven to have a real positive impact on the progress of MSMEs. Then the role of academics has a significant influence on the development of micro, small and medium enterprises (MSMEs).